The Journey for Being Pro-feminist Male Ulama: A Study among Four Indonesian Ulama - Nur Hasyim; Kilau Mentari Maulida; Luksi Visita; Zaimatus Sa’diyah (JSW (Jurnal Sosiologi Walisongo), 2025)
Male ulama have significantly influenced the feminist movement in Indonesia by providing religious interpretations that are attuned to women's experiences and actively addressing injustices faced by women. This research delves into the transformative journeys of four male ulama as they adopted pro-feminist stances and engaged with the feminist movement. Utilizing a phenomenological approach and in-depth interviews for data collection, the study focuses on how these ulama promote gender justice and embrace feminist principles. The findings reveal that the journey to pro-feminism for these ulama involves multiple phases: recognizing sensitizing events, cultivating feminist consciousness, reinforcing feminist values, and taking tangible actions against women's injustices. In their advocacy for gender justice, these ulama have crafted a methodology for interpreting religious texts that centers women's experiences as crucial to understanding faith. This interpretative approach not only supports a gender-just mindset but also seeks to integrate gender justice principles into daily practices. Ultimately, the study illustrates the essential roles male ulama play in fostering a pro-feminist environment and encouraging societal change regarding gender issues in Indonesia.